Cognitive Biases in Understanding the Influence of Shale Gas Exploitation: From Environmental and Economic Perspectives - Hu, Hui; Lin, Jingtong; Liu, Lu; Wu, Yufeng (Frontiers in Energy Research, 2021)
Shale gas is expected to be an effective alternative when the supply of conventional natural gas is dwindling. People tend to have higher expectations for shale gas exploitation. However, the promotion of large-scale shale gas exploitation does not seem to be as good as it seems, since the special extraction technology - hydraulic fracturing – inevitably does harm to local environment, which caused the cognitive biases. This paper reviews studies that estimate the environmental and economic influence of fracturing process in the U.S. and China to help people have a better understanding of shale gas exploitation. It summarizes the methodological issues and results of main projections in literature. There are shared problems in evaluating the exact influence of shale gas development due to limited identification method, data sources and advancing exploitation technology. Additionally, there are little research that monetize the carbon and water body influence of shale gas development in social benefit or economic benefit accounting. Though varies significantly across various plays and parameter compared with conventional gases, previous researches indicate that water use for shale gas development will not affect the local water supply vastly, and the ultimate influence relies on the water management method. Moreover, compared with conventional natural gas and other energy resources, freshwater consumption of shale gas exploration is dwindling with the progress of exploration technology, while its life-cycle GHG emissions is greater in the long term.